2021
DOI: 10.1016/j.jcyt.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Standardized xeno- and serum-free culture platform enables large-scale expansion of high-quality mesenchymal stem/stromal cells from perinatal and adult tissue sources

Abstract: Background aims: Mesenchymal stem/stromal cells (MSCs) are of interest for the treatment of graft-versushost disease, autoimmune diseases, osteoarthritis and neurological and cardiovascular diseases. Increasing numbers of clinical trials emphasize the need for standardized manufacturing of these cells. However, many challenges related to diverse isolation and expansion protocols and differences in cell tissue sources exist. As a result, the cell products used in numerous trials vary greatly in characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 36 publications
3
61
0
Order By: Relevance
“…In our previous study, we demonstrated that MSCs from perinatal and adult sources behaved differently even when they were cultured under a standardise culture platform (xeno-free and serum-free). 23 Therefore, although it seems that MSCs derived from different sources might show similar effects on COPD-induced animal models, we believe that the source of MSCs might play a role in the level of the therapy effectiveness and their mechanism of action might also different, especially when they are exposed to COPD-related microenvironment.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In our previous study, we demonstrated that MSCs from perinatal and adult sources behaved differently even when they were cultured under a standardise culture platform (xeno-free and serum-free). 23 Therefore, although it seems that MSCs derived from different sources might show similar effects on COPD-induced animal models, we believe that the source of MSCs might play a role in the level of the therapy effectiveness and their mechanism of action might also different, especially when they are exposed to COPD-related microenvironment.…”
Section: Discussionmentioning
confidence: 90%
“…Thirty UC samples were obtained from healthy women with an uncomplicated, at term pregnancy who underwent serological testing, including tests for HIV, cytomegalovirus, Epstein-Barr virus, hepatitis A virus, hepatitis B virus, hepatitis C virus, syphilis, and chlamydia, at 38 weeks of pregnancy, as shown in previous study. 23 The UC tissues were collected at delivery and transferred to the Stem Cell Core Facility at the Vinmec Research Institute of Stem Cell and Gene Technology under ISO 14 644–1 (certification number: CR61119-1). To generate a UC-MSC line for the current study, a single eligible UC tissue will be processed, isolated and cultured under xeno-free and serum-free conditions as previously described.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the proliferative capability of ADMSCs, cells were seeded with the density of 5,000 cells/cm 2 in T25 asks (Nunc) and cultured up to passage 7 as previously described [35]. Experiments were performed in triplicate for each donor.…”
Section: Growth Curvementioning
confidence: 99%
“…Cells were seeded in triplicate in a six-well dish at the concentration of 20 cells/cm 2 and cultured in the respective media (PS or SM) for 10 to 14 days as previously described [35]. Cells were xed in Methanol (Merck, Germany) and stained with Giemsa solution (Merck, Germany), both for 5 minutes at room temperature.…”
Section: Colony-forming Unit (Cfu) Assaymentioning
confidence: 99%